Porcelain Fused to Metal Bridge pada Gigi Posterior - Pramudya Raditya Prihandaru; Sri Oetami (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Permanent tooth loss is a common oral health problem experienced by patients. This condition can be caused by pathological conditions such as tooth decay, leading to tooth extraction. Rehabilitation treatment for partial posterior tooth loss aims to restore masticatory function, maintain occlusal relationships and periodontal health, and improve aesthetics. A 34-year-old man came with a complaint that his lower right posterior tooth had been extracted and wanted a permanent dentures to replace his missing tooth. The intraoral and periapical radiograph examination revealed that 46 was missing, and 47 had enamel caries. The diagnosis for 46 was determined to be partial edentulous. The treatment plan was a PFM fixed-fixed bridge with a sanitary pontic for 46, a rigid connector, and a full crown retainer for 45 and 47. In this case, the choice of PFM bridge is based on several considerations, i.e., high chewing loads, relatively low cost, and high long-term success. The PFM bridge has been the primary choice for posterior tooth rehabilitation, due to its durability and cost-effectiveness.